Auditory-somatosensory multisensory interactions in front and rear space. - Zampini, M; Torresan, D; Spence, C; Murray, M (2007)
The information conveyed by our senses can be combined to facilitate perception and behaviour. One focus of recent research has been on the factors governing such facilitatory multisensory interactions. The spatial register of neuronal receptive fields (RFs) appears to be a prerequisite for multisensory enhancement. In terms of auditory-somatosensory (AS) interactions, facilitatory effects on simple reaction times and on brain responses have been demonstrated in caudo-medial auditory cortices, both when auditory and somatosensory stimuli are presented to the same spatial location and also when they are separated by 100 degrees in frontal space. One implication is that these brain regions contain large spatial RFs. The present study further investigated this possibility and, in particular, the question of whether AS interactions are restricted to frontal space, since recent research has revealed some fundamental differences between the sensory processing of stimuli in front and rear space. Twelve participants performed a simple reaction time task to auditory, somatosensory, or simultaneous auditory-somatosensory stimuli. The participants placed one of their arms in front of them and the other behind their backs. Loudspeakers were placed close to each hand. Thus, there were a total of eight stimulus conditions - four unisensory and four multisensory - including all possible combinations of posture and loudspeaker location. A significant facilitation of reaction times (RTs), exceeding that predicted by probability summation, was obtained following multisensory stimulation, irrespective of whether the stimuli were in spatial register or not. These results are interpreted in terms of the likely RF organization of previously identified auditory-somatosensory brain regions.